1982
DOI: 10.1119/1.13006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electric fields of rotating charge distributions

Abstract: A charge distribution with axial symmetry is allowed to rotate with constant angular velocity around the axis of symmetry. The magnetic field of the resultant current density is calculated in terms of the electrostatic field of the charge distribution. The relation is of greatest utility in the calculation of the magnetic field of a rotating spherically symmetric charge distribution in terms of its electrostatic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…F( r) = e r F(r), being e r the unit radial vector (Marsh 1982). The magnetic field is thus given by B( r) = B r e r + B θ e θ ,…”
Section: Influence Of the Rotationally Induced Magnetic Fieldmentioning
confidence: 99%
“…F( r) = e r F(r), being e r the unit radial vector (Marsh 1982). The magnetic field is thus given by B( r) = B r e r + B θ e θ ,…”
Section: Influence Of the Rotationally Induced Magnetic Fieldmentioning
confidence: 99%
“…Marsh [19] showed that the magnetic field, B s , measured by an inertial observer, due to a simple circular loop of rotating charge, expressed in terms of a cylindrical polar coordinate system, is…”
Section: Discussionmentioning
confidence: 99%
“…al. 18 using the technique developed by Marsh 19 . In particular, for such a rotating system with a period of 10ms we have obtained a magnetic field of order of the critical field near the surface and analyzed the magnetic lines of forces.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of spherical symmetry, F ( r) may be taken as radial (see Marsh 19 ). Writing F ( r) = e r F (r), where e r is the unit radial vector, one has…”
Section: Rotating Nuclear Matter Cores Of Stellar Dimensions In Classmentioning
confidence: 99%